Acupressure in patients with seasonal allergic rhinitis: a randomized controlled exploratory trial - Lukas Israel; Gabriele Rotter; Ulrike Förster-Ruhrmann; Josef Hummelsberger; Rainer Nögel; Andreas Michalsen; Tatjana Tissen-Diabaté; Sylvia Binting; Thomas Reinhold; Miriam Ortiz; Benno Brinkhaus (BMC, 2021)
Abstract Background Acupuncture has shown beneficial effects for seasonal allergic rhinitis (SAR); however, it is time and cost intensive. We investigated feasibility and effects of self-administered body acupressure as a self-care technique that stimulates acupuncture points with manual pressure in SAR patients. Methods We conducted a two-armed randomized controlled exploratory trial to compare effects of self-administered acupressure over 4 weeks at five acupuncture points plus rescue medication (RM) with cetirizine compared to RM alone in SAR patients. Among other outcome parameters, we assessed disease-related quality of life (Rhinitis Quality of Life Questionnaire [RQLQ]), overall SAR symptoms by a visual analogue scale (VAS) and a rescue medication score (RMS) after 4 and 8 weeks. Results Forty-one SAR patients (mean age 38.5 ± 10.0 years, n = 21, 51.2% women) were randomized. Compared to RM alone (n = 21), acupressure plus RM (n = 20) was associated with relevant improvements after 4 weeks, shown by the difference between groups in adjusted means of RQLQ: − 0.9 points (95% CI − 1.6 to − 0.2; p = 0.011) and VAS overall SAR symptoms: − 21.6 mm (95% CI − 36.3 to − 6.8; p = 0.005). The RMS was lower in the acupressure group than in the control group: 1.9 points (95% CI − 3.8 to − 0.1; p = 0.120). Group differences decreased slightly until week 8. The acupressure was feasible and safe. Conclusion Results of this exploratory study indicate that self-applied acupressure is feasible, may improve disease-specific quality of life and reduce disease-related symptoms as well as anti-allergic medication intake in SAR patients. High-quality confirmatory studies including a sham-control group are needed in the future. Trial registration DRKS-ID: DRKS00014310. Date of registration in DRKS: 2018/04/24. Investigator sponsored/initiated trial (IST/IIT): yes. Ethics approval/approval of the ethics committee: Approved (leading) Ethics Committee No. EA1/033/18, Ethik-Kommission der Charité -Universitätsmedizin Berlin. URL: https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00014310